TECHNOLOGY TO IMPROVE STUDENTS’ CREATIVE THINKING BASED ON AN INTERNATIONAL ASSESSMENT PROGRAM - Ibragimova Khurshida Sherali qizi (International Engineering Journal For Research & Development, 2021)
This article describes the work done in PISA 2022 to further enhance and develop students' creative thinking, the main purpose, importance, specific limitations of creative thinking and the personal factors that shape creative thinking.